Achille Funi in the MAC-USP colllection (L'uomo nero. Materiali per una storia delle arti della modernità, 2022)
In the last years, many studies about the foundation of the artistic institutions devoted to modern art in Brazil were published by Brazilian historiography. These institutions were established thanks to the relationship between the Paulist art critic Sérgio Milliet and the industrialist Francisco Matarazzo Sobrinho (of Italian descent) and American museum, first of all the Museum of Modern Art in New York.From this negotiation (especially in 1946), Francisco Matarazzo Sobrinho and his wife Yolanda Penteado, purchased a first group of Italian and French modern art, shipped in Brazil in 1947. This was the starting point of the collection of the Museum of Modern Art (MAM) in Sao Paulo, later moved to the University of Sao Paulo in 1963 in order to establish the Museum of Contemporary Art (MAC-USP).The essay focused on the painting L’indovina (1924) by Achille Funi, included in the collection, bought in 1946 thanks to Galleria Il Million in Milan.
Keywords: XX c. Italian Art; Achille Funi; Francisco Matarazzo Sobrinho; Yolanda Penteado